2020
DOI: 10.1038/s42255-020-00281-8
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody-negative insulin-dependent diabetes mellitus after SARS-CoV-2 infection: a case report

Abstract: Here we report a case where the manifestations of insulin-dependent diabetes occurred following SARS-CoV-2 infection in a young individual in the absence of autoantibodies typical for type 1 diabetes mellitus. Specifically, a 19-year-old white male presented at our emergency department with diabetic ketoacidosis, C-peptide level of 0.62 µg l-1 , blood glucose concentration of 30.6 mmol l-1 (552 mg dl-1) and haemoglobin A1c of 16.8%. The patient´s case history revealed probable COVID-19 infection 5-7 weeks befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
145
1
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(168 citation statements)
references
References 33 publications
6
145
1
4
Order By: Relevance
“…A recently published case report described autoantibody-negative insulin-dependent diabetes onset in a young patient who was infected by SARS-CoV-2 seven weeks before diabetes symptoms occurrence (20). Additional previous studies further support such observation(21,22).…”
Section: Introductionmentioning
confidence: 99%
“…A recently published case report described autoantibody-negative insulin-dependent diabetes onset in a young patient who was infected by SARS-CoV-2 seven weeks before diabetes symptoms occurrence (20). Additional previous studies further support such observation(21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Second, severe exacerbations of a preexisting diabetes as well as new-onset diabetes have been reported [13][14][15][16] and cases of non-immune mediated diabetes in previously healthy individuals become increasingly evident 17 . So far, it is unclear whether SARS-CoV-2 triggers immune-mediated β-cell ablation as in type 1 diabetes (T1D) or directly perturbs β-cell function leading to non-autoimmune-mediated diabetes.…”
Section: Read Full License Introductionmentioning
confidence: 99%
“…4B). This suggests that SARS-CoV-2 viral infiltration leads to pMLKL positivity, most likely associated with the necroptosis signaling pathway 24 , and might explain why type 1 diabetes has been reported after infection with SARS-CoV-2 5,6 .…”
mentioning
confidence: 97%
“…In addition to its known role on the respiratory system, the human coronavirus SARS-CoV-2 has been shown to affect the endocrine system including the pancreas [1][2][3][4] . It has been suggested that the virus can induce type 1 diabetes [5][6][7][8] . Therefore, we isolated human pancreatic islets and examined the expression of angiotensin-converting enzyme 2 (ACE2) and the protease TMPRSS2, known to be important for SARS-CoV-2 entry 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation